INVESTIGATING STUDENTS’ AFFECTIVE ENGAGEMENT ON DESCRIPTIVE WRITING ASSIGNMENT BY USING INSTAGRAM - annisa pratiwi; Fauzi Miftakh; Acep Bahrum Kamil (Journal of English Language Learning, 2020)
The traditional method of teaching and learning writing has been seen as boring. The students only write their writing assignment on their paper and it could only be read by their lecturer. Whereas in this modern era social media platforms become an important part in human daily lives, social media platforms are also used for educational purposes. One of the popular social media platforms is Instagram. This research aims to find how students' responses regarding their affective engagement toward the use of Instagram on the descriptive writing assignment. Qualitative methods and narrative inquiry were used to conduct this research. The participants of this research were 6 English Education Department students in the 8th semester at the University of Singaperbangsa Karawang. Simple random sampling was used in selecting the participants. In this research, three data collection techniques were used to collect the data: interview, students' reflective journal, and photovoice. There are three results of this research. The first is utilizing Instagram on a descriptive writing assignment makes students feel happy, enjoyable, and comfortable. The second is Instagram increases their writing interest. And the third is Instagram makes students feel engaged in the writing activity.Keywords: Affective Engagement, Instagram, Writing Descriptive Text Assignment